2017
DOI: 10.1556/650.2017.30747
|View full text |Cite
|
Sign up to set email alerts
|

Az étrend szerepe a húgyúti kövek kialakulásában és megelőzésében

Abstract: A húgyúti kövesség a fejlett országokban a metabolikus és endokrin okok mellett egyre gyakrabban fordul elő a helytelen táplálkozási szokások, az elhízás és a mozgásszegény életmód miatt. Ezért az urológusok és az alapellátásban dolgozók mindennapi munkájában kiemelt szerepet kellene, hogy kapjon az elsődleges és másodlagos prevenció. A megelőzés a testsúlykontrollon, a testmozgáson és a gyógyszeres kezelésen túl a megfelelő diétán alapul. Az étrend különböző alkotóelemei megváltoztathatják a vizelet összetéte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Ferraro and his colleagues reported that adherence to low-risk dietary and lifestyle factors was associated with more than a 50 % reduction in the incidence of stones [11]. The following points for preventing the formation of encrustations were suggested: 1) the diet should include all kinds of food, with vegetables being eaten at every meal and avoidance of an excessive intake of meat; 2) decreased salt intake because sodium intake may predispose to stones by stimulating calcium excretion; 3) increased dietary long-chain polyunsaturated fatty acids since they alter serum fatty acid concentrations and lower risk of urine stone formation [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Ferraro and his colleagues reported that adherence to low-risk dietary and lifestyle factors was associated with more than a 50 % reduction in the incidence of stones [11]. The following points for preventing the formation of encrustations were suggested: 1) the diet should include all kinds of food, with vegetables being eaten at every meal and avoidance of an excessive intake of meat; 2) decreased salt intake because sodium intake may predispose to stones by stimulating calcium excretion; 3) increased dietary long-chain polyunsaturated fatty acids since they alter serum fatty acid concentrations and lower risk of urine stone formation [12,13].…”
Section: Discussionmentioning
confidence: 99%